2012
DOI: 10.3136/fstr.18.535
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of King Oyster Mushrooms Stored with a Master Packaging System Consisting of Inner Individual Packs and an Outer Liner Bag to Be Dismantled at a Retail Display

Abstract: To better handle variable temperature regimes in produce distribution, a master packaging system consisting of a double-layered gas barrier has been applied to fresh king oyster mushrooms. A secondary master package wrapping four individual 350 g packages was designed to be dismantled when moved to the 10℃ retail display from the presale storage at 0℃. Different numbers of microperforations (10, 15 and 20) were tested on the inner individual packages as a control variable to create and maintain beneficial modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Good packaging also has an impact on the product that lasts longer and is not easily damaged. Several food packaging technologies can be used, including master packaging [22], active packaging [23], or smart packaging [24]. The high complexity of the valueadding process Lack of a holistic view of valueadding processes in FSC Lack of communication Another contribution to reducing food loss and waste is packaging transport concepts and network planning.…”
Section: Fig 1 Supply Chain Of California Papayamentioning
confidence: 99%
“…Good packaging also has an impact on the product that lasts longer and is not easily damaged. Several food packaging technologies can be used, including master packaging [22], active packaging [23], or smart packaging [24]. The high complexity of the valueadding process Lack of a holistic view of valueadding processes in FSC Lack of communication Another contribution to reducing food loss and waste is packaging transport concepts and network planning.…”
Section: Fig 1 Supply Chain Of California Papayamentioning
confidence: 99%
“…Optimal MA condition suggested for quality preservation varies with literatures or sources. In this study of MAP design, MA of 1% O 2 and 10% CO 2 , reported to be beneficial, was used as a target for the optimization [21,22] (Table 1). The upper limit of CO 2 concentration range 15% was adopted as the tolerance limit in the optimization.…”
Section: Package Of King Oyster Mushroommentioning
confidence: 99%